Nanoparticulate Carrier Drug Delivery System: A Versatile Tool for Drug Administration - Kamat, Viraj; Pomaje, Madan; Patil, Ashwini; Tikam, Shruti; Burunkar, Vivek (International Journal of Membrane Science and Technology, 2023)
For over 25 years, the biomedical field has employed a range of adaptable drug delivery systems, including solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs). Because they naturally pass the blood-brain barrier (BBB), SLNs and NLCs have been used to treat a variety of illnesses, including cardiovascular and cerebrovascular. For the latter, they are regarded as a standard treatment. The most common brain diseases—brain cancer, ischemic stroke, Alzheimer's, Parkinson's, and multiple sclerosis—are discussed in this review. Next, the fundamental methods for creating SLNs and NLCs are covered. A thorough analysis of the published research over the previous seven years is also conducted, focusing on the use of SLNs and NLCs for both active as well as passive targeting in the treatment of neurological conditions and glioblastoma multiforme and other brain tumors. Lastly, a succinct overview of the benefits, drawbacks, and potential applications of these nanocarriers is provided in an effort to provide readers with an understanding of the obstacles that must be surmounted in order to produce a delivery system that is both highly therapeutically effective and free of the constraints of currently available nano systems.